The obstacle course to economic independence: Labour force participation for people with disabilities in Australia - Twigger, Michelle (Economic Society of Australia, 2010)
The 2009 Australian National Disability Strategy Consultation Report (NDSCR) paints a tragic picture of what it is to be disabled in a first world nation in the 21st Century. Despite the Australian Government passing the national Disability Discrimination Act in 1992 designed to eliminate discrimination on the grounds of disability in areas of education, employment, access and law, the legislation has failed to live up to its objective of ensuring ?that persons with disabilities have the same fundamental rights as the rest of the community?. The 2003 Survey of Disability and Aging found that the 20% of Australians classed as disabled had significantly lower levels of education, higher levels of unemployment and the gross personal household income was half that of persons without disability. This report builds on past research into disability and labour force participation, investigates whether there have been any significant improvements in employment outcomes for disabled Australians over the past decade and considers the social and economic implications for policy makers.